Rescue missions of starved children from Bosnia and Herzegovina during the World War I: the case of cooperation with the Kingdom of Croatia and Slavonia - Matković, Stjepan; Miloš, Edi (Historical Thought, 2025)
During the World War I several rescue missions were carried out for the sake of children in the poor areas of the south-eastern part of the AustroHungarian territory, e. g., Bosnia-Herzegovina, Dalmatia, and Istria. In BosniaHerzegovina, whose borders had been the theatre of military operation against Serbia and Montenegro at the beginning of the war, this humanitarian action was led in accordance between the land governments of Croatia and BosniaHerzegovina, approved by army officials and organized by humanitarian associations from Zagreb established in the pre-war years that were involved in child care and protection, as well as by the Central Committee for the Defence of Families in the Wars and of soldiers who died in combat. The authorities did not have any influence on the choice of the displaced children, some of whom had lost their fathers on the battlefileds, or even both parents due to diseases or starvation. As they were Orthodox, Muslim, and Catholic, the representatives of all three confessional communities were requested to agree about children transports and their displacements in different places of municipal districts and counties in Slavonia region. In this paper special attention is paid to the Muslim children who were situated in the boarding-school in Vinkovci. According to the documents collected by Eugen Sladović, who was the under secretary of BosnianHerzegovinian Governement at that time and officially authorized by its decree to control children’s transports and schooling, one can reconstruct most of childhood education, their religious upbringing and living conditions. Sladović’s papers show who participated in child care of Muslims, either from the Croatian or BosnianHerzegovinian side. In the end, the authors bring three lists with the personal names of Muslims children, including also the names of deceased among them and returnees to their homeland.